Increasing the working hours of nurses and teachers: Evidence from a discrete choice experiment - Melline Somers; Tom Stolp; Francesca Burato; Wim Groot; Frits van Merode; Melvin Vooren (PLoS ONE, 2026)
The healthcare and education sectors suffer from shortages of nurses and teachers. Extending their working hours has often been proposed as a solution to reduce shortages. In this study, we conduct a discrete choice experiment (DCE) in the Netherlands to elicit nurses’ and teachers’ preferences for different jobs and working conditions. We present both nurses and teachers with nine hypothetical choice sets, each consisting of two jobs that differ in seven observable job attributes. From the DCE, we infer workers’ willingness to pay for these different job characteristics. Moreover, we calculate how many additional hours they would be willing to work if a specific workplace condition were met. We find that both nurses and teachers most negatively value high work pressure. Spending a lot of time on patient-related tasks is highly valued by nurses, followed by having more control over working hours. Next to work pressure, teachers place significant importance on receiving social support from both colleagues and managers. Part-time teachers and nurses require a 23 and 21 percent increase in net hourly wages to accept a full-time working contract, respectively.